Development of a human-guided robotic manipulation system - Sim, Chin Luk (2014)
Human-guided robot interaction is a scientific study on how humans can control the robot. Information on the surrounding environment is essential for a robot to actuate autonomously. Majority of the robots are seen to be operating in industrial purposes and an increasing number are used to aid in fields such as mine and bomb detection, military battle, rescue and search mission. As the surrounding environment of the robot‟s application are sometimes unknown to the robot, the guidance from human is important to ensure the success of the robot operation. In this project, a human-guided robotic manipulation system will be developed. As human is able to react intelligently to unforeseen changes in the real world and robot is able to perform precision tasks or carry heavy loads that are beyond the capability of human, a control method will be developed to take advantage of both the human knowledge and the robot‟s ability. In situations where human control action is required, the system should allow more flexibility. In cases where precision is required or when human intervention is not expected, the system should let the robot to take control. The control method will be implemented on an industrial robot (Sony SCARA industrial robot) using a kinect sensor which will detect the robot, human and the surrounding environment.